ANALISIS LITERASI INFORMASI PADA KETERAMPILAN MENULIS KRITIS DAN ILMIAH MAHASISWA PENDIDIKAN BAHASA INDONESIA UHKBPNP - S, Monalisa Frince (Unversitas Katolik Santo Thomas, 2020)
This study aims to describe the information literacy ability of Indonesian language education students at the University of HKBP Nommensen Pematangsiantar on the subject of critical and scientific writing skills. This study analyzes the information literacy ability using the Seven Pillars Model created by the Standing Conferences of National and University Libraries (SCONUL) which consists of: (1) Identify (understand information needs, (2) Scope (determine the type of information, characteristics, challenges), (3) Plan (determine the search strategy), (4) Gather (do a search, access information), (5) Evaluate (Relevance, accuracy, comparison, (6) Manage (manage information, quote, compile a bibliography, know ethics using information , and (7) present (compile information products in the right form and present) .This type of research uses descriptive research.The method used in this study is a qualitative research method. The data collection techniques in this study are interviews and observation.Keywords: writing, critical and scientific, information literacy